'Truth of Soul's Life' or 'Distorted Optics'?: A Historiography of the Genevan Summer of 1816. (2nd July 2016) - Vincent, Patrick
Abstract: Despite all the scholarly work on Lord Byron and the Shelleys' stay in Switzerland in 1816, legends and apocryphal stories continue to proliferate, due in part to its many fictional representations but also to differences in the main protagonists' reporting of events. While the Shelleys privileged a romanticized account faithful to what Mary Shelley would later call the 'truth of soul's life', Byron lamented that 'distorted optics' falsified the summer's history. Organized into a subchapter on Geneva and another on the various tours in Switzerland, this essay reviews the Genevan summer's main sources and establishes its chronology, weighing the validity of anecdotes and evaluating how some biographers and critics have marshaled the evidence. Although Byron tried to control its narrative, the summer of 1816 became inscribed in European culture as a lieu de mémoire more romantically suggestive than mere fact, helping to explain why it still haunts us today.